Validation of Laboratory-Developed Molecular Assays for Infectious Diseases - Burd, Eileen M. (American Society for Microbiology (ASM), 2010)
Summary: Molecular technology has changed the way that clinical laboratories diagnose and manage many infectious diseases. Excellent sensitivity, specificity, and speed have made molecular assays an attractive alternative to culture or enzyme immunoassay methods. Many molecular assays are commercially available and FDA approved. Others, especially those that test for less common analytes, are often laboratory developed. Laboratories also often modify FDA-approved assays to include different extraction systems or additional specimen types. The Clinical Laboratory Improvement Amendments (CLIA) federal regulatory standards require clinical laboratories to establish and document their own performance specifications for laboratory-developed tests to ensure accurate and precise results prior to implementation of the test. The performance characteristics that must be established include accuracy, precision, reportable range, reference interval, analytical sensitivity, and analytical specificity. Clinical laboratories are challenged to understand the requirements and determine the types of experiments and analyses necessary to meet the requirements. A variety of protocols and guidelines are available in various texts and documents. Many of the guidelines are general and more appropriate for assays in chemistry sections of the laboratory but are applied in principle to molecular assays. This review presents information that laboratories may consider in their efforts to meet regulatory requirements.